2017
DOI: 10.1038/onc.2017.246
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide screen for differentially methylated long noncoding RNAs identifies Esrp2 and lncRNA Esrp2-as regulated by enhancer DNA methylation with prognostic relevance for human breast cancer

Abstract: The majority of long noncoding RNAs (lncRNAs) is still poorly characterized with respect to function, interactions with protein-coding genes, and mechanisms that regulate their expression. As for protein-coding RNAs, epigenetic deregulation of lncRNA expression by alterations in DNA methylation might contribute to carcinogenesis. To provide genome-wide information on lncRNAs aberrantly methylated in breast cancer we profiled tumors of the C3(1) SV40TAg mouse model by MCIp-seq (Methylated CpG Immunoprecipitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 121 publications
(152 reference statements)
4
35
0
Order By: Relevance
“…2b). According to previous reports [29], qPCR analyses with primers detecting variants v1-4 or v1+2 revealed that all variants together had about 20-fold higher expression than the long variants v1+2 both in MIN6 cells and islets, suggesting that the short variant v4 represents the major transcript ( Fig. 2c).…”
Section: Characterisation Of Roitsupporting
confidence: 78%
“…2b). According to previous reports [29], qPCR analyses with primers detecting variants v1-4 or v1+2 revealed that all variants together had about 20-fold higher expression than the long variants v1+2 both in MIN6 cells and islets, suggesting that the short variant v4 represents the major transcript ( Fig. 2c).…”
Section: Characterisation Of Roitsupporting
confidence: 78%
“…Recent studies have demonstrated that aberrant DNA methylation of promoters may be an epigenetic regulator of lncRNA expression . In the present study, we found frequent hypermethylation of C5orf66‐AS1 in the three CpG islands, and the hypermethylation of the CpG sites around the transcription start site was more tumor specific and might be associated with the inactivation of C5orf66‐AS1.…”
Section: Discussionsupporting
confidence: 66%
“…RNA m 6 A methylation is reversible and can be demethylated by ALKBH5 or FTO [17,18]. The m 6 A mRNA modification has been studied extensively; however, the importance of lncRNA methylation has remained elusive [19]. We found that KCNK15-AS1 underwent m 6 A methylation in pancreatic cells HPDE6-C7, MIA-PaCa-2, and BxPC-3.…”
Section: Discussionmentioning
confidence: 89%